The acute potentiating effects of back squats on athlete performance - Crewther, B. T.; Kilduff, L. P.; Cook, C. J.; Middleton, M. K. (The Journal of Strength and Conditioning Research, 2011)
This study examined the acute potentiating effects of back squats on athlete performance with a specific focus on movement specificity and the individual timing of potentiation. Nine subelite male rugby players performed 3 protocols on separate occasions using a randomized, crossover, and counterbalanced design. Each protocol consisted of performance testing before a single set of 3 repetition maximum (3RM) back squats, followed by retesting at 15 seconds, 4, 8, 12, and 16 minutes. The 3 tests were countermovement jumps (CMJs), sprint performance (5 and 10 m), and 3-m horizontal sled pushes with a 100-kg load. Relationships between the individual changes in salivary testosterone and cortisol concentrations and performance were also examined. The 3RM squats significantly (p < 0.001) improved CMJ height at 4 (3.9 ± 1.9%), 8 (3.5 ± 1.5%), and 12 (3.0 ± 1.4%) minutes compared with baseline values, but no temporal changes in sprinting and sled times were identified. On an individual level, the peak relative changes in CMJ height (6.4 ± 2.1%, p < 0.001) were greater than the 3-m sled (1.4 ± 0.6%), 5-m (2.6 ± 1.0%), and 10-m sprint tests (1.8 ± 1.0%). In conclusion, a single set of 3RM squats was found effective in acutely enhancing CMJ height in the study population, especially when the recovery period was individualized for each athlete. The study results also suggest that the potentiating effects of squats may exhibit some degree of movement specificity, being greater for those exercises with similar movement patterns. The current findings have practical implications for prescribing warm-up exercises, individualizing training programs, and for interpreting postactivation potentiation research.